Ultrasonography in diagnosis of sexual development delay of girls and teenagers having diabetes mellitus of the 1st type - N. M. Kondratyeva; V. D. Zavadovskaya; E. B. Kravets; E. V. Gorbatenko; L. S. Strelis (Бюллетень сибирской медицины)
Girls-teenagers (n = 85) aged from 8 to 18 years having diabetes mellitus (DM) of the 1st type were investigated using ultrasonography method. Based upon decreasing and disproportion of the body and neck of the uterus, changed Mecho thickness and ovaries structure, different parameter of blood flow, we worked out classification of the four stages of sexual development delay (SDD) (0 stage in 15 girls, I stage in 26 girls, II stage in 20 girls and III stage in 21 girls). Comparative analysis of clinical and ultrasound studies showed the advantage of ultrasound study to assess status of internal genital organs in girls and teenagers having DM. Investigation performed based upon E. Tanner classification revealed SDD 40 girls, bimanual examination in 45 girls, sonography method — in 82 girls. The given ultrasound classification of sexual development delay in girls-teenagers having DM of the 1st type contributes to diagnosis and prescribing timely effective correction therapy.